Graphite, graphene on SiC, and graphene nanoribbons: Calculated images with a numerical FM-AFM - Castanié, Fabien; Nony, Laurent; Gauthier, Sébastien; Bouju, Xavier (Beilstein Journal of Nanotechnology, 2012)
Background: Characterization at the atomic scale is becoming an achievable task for FM-AFM users equipped, for example, with a qPlus sensor. Nevertheless, calculations are necessary to fully interpret experimental images in some specific cases. In this context, we developed a numerical AFM (n-AFM) able to be used in different modes and under different usage conditions.Results: Here, we tackled FM-AFM image calculations of three types of graphitic structures, namely a graphite surface, a graphene sheet on a silicon carbide substrate with a Si-terminated surface, and finally, a graphene nanoribbon. We compared static structures, meaning that all the tip and sample atoms are kept frozen in their equilibrium position, with dynamic systems, obtained with a molecular dynamics module allowing all the atoms to move freely during the probe oscillations.Conclusion: We found a very good agreement with experimental graphite and graphene images. The imaging process for the deposited nanoribbon demonstrates the stability of our n-AFM to image a non-perfectly planar substrate exhibiting a geometrical step as well as a material step.
Keywords: calculations; FM-AFM; graphene; graphite; image; nanoribbon

(untitled) - Giessibl, F. J. (Rev. Mod. Phys., 2003)

(untitled) - Barth, C.; Foster, A. S.; Henry, C. R.; Shluger, A. L. (Adv. Mater., 2011)

(untitled) - Gross, L. (Nat. Chem., 2011)

(untitled) - Lauritsen, J. V.; Reichling, M. (J. Phys.: Condens. Matter, 2010)

(untitled) - Giessibl, F. J. (Science, 1995)

(untitled) - Giessibl, F. J.; Hembacher, S.; Bielefeldt, H.; Mannhart, J. (Science, 2000)

(untitled) - Giessibl, F. J. (Mater. Today, 2005)

(untitled) - Giessibl, F. J.; Herz, M.; Mannhart, J. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Sugimoto, Y.; Pou, P.; Abe, M.; Jelinek, P.; Pérez, R.; Morita, S.; Custance, Ó. (Nature, 2007)

(untitled) - Morita, K.; Sugimoto, Y.; Sasagawa, Y.; Abe, M.; Morita, S. (Nanotechnology, 2010)

(untitled) - Sugimoto, Y.; Nakajima, Y.; Sawada, D.; Morita, K.-i.; Abe, M.; Morita, S. (Phys. Rev. B, 2010)

(untitled) - Sugimoto, Y.; Yi, I.; Morita, K.-i.; Abe, M.; Morita, S. (Appl. Phys. Lett., 2010)

(untitled) - Kolodziej, J. J.; Such, B.; Szymonski, M.; Krok, F. (Phys. Rev. Lett., 2003)

(untitled) - Kolodziej, J. J.; Such, B.; Szymonski, M. (Phys. Rev. B, 2005)

(untitled) - Eguchi, T.; Fujikawa, Y.; Akiyama, K.; An, T.; Ono, M.; Hashimoto, T.; Morikawa, Y.; Terakura, K.; Sakurai, T.; Lagally, M. G.; Hasegawa, Y. (Phys. Rev. Lett., 2004)

(untitled) - Hamm, G.; Barth, C.; Becker, C.; Wandelt, K.; Henry, C. R. (Phys. Rev. Lett., 2006)

(untitled) - Heyde, M.; Kulawik, M.; Rust, H.-P.; Freund, H.-J. (Phys. Rev. B, 2006)

(untitled) - Barth, C.; Henry, C. R. (Phys. Rev. Lett., 2003)

(untitled) - Heyde, M.; Simon, G. H.; Rust, H.-P.; Freund, H.-J. (Appl. Phys. Lett., 2006)

(untitled) - Bieletzki, M.; Hynninen, T.; Soini, T. M.; Pivetta, M.; Henry, C. R.; Foster, A. S.; Esch, F.; Barth, C.; Heiz, U. (Phys. Chem. Chem. Phys., 2010)

(untitled) - Hoffmann, R.; Kantorovich, L. N.; Baratoff, A.; Hug, H. J.; Güntherodt, H.-J. (Phys. Rev. Lett., 2004)

(untitled) - Barth, C.; Henry, C. R. (Phys. Rev. Lett., 2008)

(untitled) - Hoffmann, R.; Weiner, D.; Schirmeisen, A.; Foster, A. S. (Phys. Rev. B, 2009)

(untitled) - Langewisch, G.; Fuchs, H.; Schirmeisen, A. (Nanotechnology, 2010)

(untitled) - Kawai, S.; Canova, F. F.; Glatzel, T.; Foster, A. S.; Meyer, E. (Phys. Rev. B, 2011)

(untitled) - Schütte, J.; Rahe, P.; Tröger, L.; Rode, S.; Bechstein, R.; Reichling, M.; Kühnle, A. (Langmuir, 2010)

(untitled) - Lauritsen, J. V.; Foster, A. S.; Olesen, G. H.; Christensen, M. C.; Kühnle, A.; Helveg, S.; Rostrup-Nielsen, J. R.; Clausen, B. S.; Reichling, M.; Besenbacher, F. (Nanotechnology, 2006)

(untitled) - Rahe, P.; Bechstein, R.; Schütte, J.; Ostendorf, F.; Kühnle, A. (Phys. Rev. B, 2008)

(untitled) - Yurtsever, A.; Sugimoto, Y.; Abe, M.; Morita, S. (Nanotechnology, 2010)

(untitled) - Hoffmann, R.; Lantz, M. A.; Hug, H. J.; van Schendel, P. J. A.; Kappenberger, P.; Martin, S.; Baratoff, A.; Güntherodt, H.-J. (Phys. Rev. B, 2003)

(untitled) - Hoffmann, R.; Lantz, M. A.; Hug, H. J.; van Schendel, P. J. A.; Kappenberger, P.; Martin, S.; Baratoff, A.; Güntherodt, H.-J. (Appl. Surf. Sci., 2002)

(untitled) - Venegas de la Cerda, M. A.; Abad, J.; Madgavkar, A.; Martrou, D.; Gauthier, S. (Nanotechnology, 2008)

(untitled) - Kawai, S.; Glatzel, T.; Koch, S.; Such, B.; Baratoff, A.; Meyer, E. (Phys. Rev. Lett., 2009)

(untitled) - Ruschmeier, K.; Schirmeisen, A.; Hoffmann, R. (Phys. Rev. Lett., 2008)

(untitled) - Such, B.; Glatzel, T.; Kawai, S.; Koch, S.; Meyer, E. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2010)

(untitled) - Hoffmann, R.; Barth, C.; Foster, A. S.; Shluger, A. L.; Hug, H. J.; Güntherodt, H.-J.; Nieminen, R. M.; Reichling, M. (J. Am. Chem. Soc., 2005)

(untitled) - Allers, W.; Schwarz, A.; Schwarz, U. D.; Wiesendanger, R. (Appl. Surf. Sci., 1999)

(untitled) - Hölscher, H.; Allers, W.; Schwarz, A.; Schwarz, U. D.; Wiesendanger, R. (Phys. Rev. B, 2000)

(untitled) - Hölscher, H.; Schwarz, A.; Allers, W.; Schwarz, U. D.; Wiesendanger, R. (Phys. Rev. B, 2000)

(untitled) - Hembacher, S.; Giessibl, F. J.; Mannhart, J.; Quate, C. F. (Proc. Natl. Acad. Sci. U. S. A., 2003)

(untitled) - Hembacher, S.; Giessibl, F. J.; Mannhart, J.; Quate, C. (Phys. Rev. Lett., 2005)

(untitled) - Albers, B. J.; Schwendemann, T. C.; Baykara, M. Z.; Pilet, N.; Liebmann, M.; Altman, E. I.; Schwarz, U. D. (Nat. Nanotechnol., 2009)

(untitled) - Kawai, S.; Kawakatsu, H. (Phys. Rev. B, 2009)

(untitled) - Ondráček, M.; Pou, P.; Rozsíval, V.; González, C.; Jelínek, P.; Pérez, R. (Phys. Rev. Lett., 2011)

(untitled) - Loppacher, C.; Guggisberg, M.; Pfeiffer, O.; Meyer, E.; Bammerlin, M.; Lüthi, R.; Schlittler, R.; Gimzewski, J. K.; Tang, H.; Joachim, C. (Phys. Rev. Lett., 2003)

(untitled) - Nony, L.; Gnecco, E.; Baratoff, A.; Alkauskas, A.; Bennewitz, R.; Pfeiffer, O.; Maier, S.; Wetzel, A.; Meyer, E.; Gerber, C. (Nano Lett., 2004)

(untitled) - Yoda, T.; Ichii, T.; Fukuma, T.; Kobayashi, K.; Yamada, H.; Matsushige, K. (Jpn. J. Appl. Phys., 2004)

(untitled) - Ashino, M.; Schwarz, A.; Behnke, T.; Wiesendanger, R. (Phys. Rev. Lett., 2004)

(untitled) - Burke, S. A.; Mativetsky, J. M.; Hoffmann, R.; Grütter, P. (Phys. Rev. Lett., 2005)

(untitled) - Fendrich, M.; Kunstmann, T.; Paulkowski, D.; Möller, R. (Nanotechnology, 2007)

(untitled) - Ashino, M.; Obergfell, D.; Haluška, M.; Yang, S.; Khlobystov, A. N.; Roth, S.; Wiesendanger, R. (Nat. Nanotechnol., 2008)

(untitled) - Gross, L.; Mohn, F.; Moll, N.; Liljeroth, P.; Meyer, G. (Science, 2009)

(untitled) - Gross, L.; Mohn, F.; Moll, N.; Meyer, G.; Ebel, R.; Abdel-Mageed, W. M.; Jaspars, M. (Nat. Chem., 2010)

(untitled) - Schütte, J.; Bechstein, R.; Rahe, P.; Langhals, H.; Rohlfing, M.; Kühnle, A. (Nanotechnology, 2011)

(untitled) - Pawlak, R.; Kawai, S.; Fremy, S.; Glatzel, T.; Meyer, E. (ACS Nano, 2011)

(untitled) - Mohn, F.; Gross, L.; Meyer, G. (Appl. Phys. Lett., 2011)

(untitled) - Kawai, S.; Pawlak, R.; Glatzel, T.; Meyer, E. (Phys. Rev. B, 2011)

(untitled) - Hinaut, A.; Lekhal, K.; Aivazian, G.; Bataillé, S.; Gourdon, A.; Martrou, D.; Gauthier, S. (J. Phys. Chem. C, 2011)

(untitled) - Chiutu, C.; Stannard, A.; Sweetman, A. M.; Moriarty, P. (Chem. Commun., 2011)

(untitled) - Guillermet, O.; Gauthier, S.; Joachim, C.; de Mendoza, P.; Lauterbach, T.; Echavarren, A. (Chem. Phys. Lett., 2011)

(untitled) - Giessibl, F. J. (Appl. Phys. Lett., 2000)

(untitled) - Giessibl, F. J.; Pielmeier, F.; Eguchi, T.; An, T.; Hasegawa, Y. (Phys. Rev. B, 2011)

(untitled) - Couturier, G.; Boisgard, R.; Nony, L.; Aimé, J. P. (Rev. Sci. Instrum., 2003)

(untitled) - Couturier, G.; Aimé, J. P.; Salardenne, J.; Boisgard, R. (Eur. Phys. J.: Appl. Phys., 2001)

(untitled) - Polesel-Maris, J.; Gauthier, S. (J. Appl. Phys., 2005)

(untitled) - Trevethan, T.; Kantorovich, L.; Polesel-Maris, J.; Gauthier, S. (Nanotechnology, 2007)

(untitled) - Nony, L.; Baratoff, A.; Schär, D.; Pfeiffer, O.; Wetzel, A.; Meyer, E. (Phys. Rev. B, 2006)

(untitled) - Castanié, F.; Nony, L.; Gauthier, S.; Bouju, X. (2012)
(to be submitted for publication).

(untitled) - Geim, A. K. (Rev. Mod. Phys., 2011)

(untitled) - Novoselov, K. S. (Rev. Mod. Phys., 2011)

(untitled) - Avouris, P. (Nano Lett., 2010)

(untitled) - Rümmeli, M. H.; Rocha, C. G.; Ortmann, F.; Ibrahim, I.; Sevincli, H.; Börrnert, F.; Kunstmann, J.; Bachmatiuk, A.; Pötschke, M.; Shiraishi, M.; Meyyappan, M.; Büchner, B.; et al. (Adv. Mater., 2011)

(untitled) - Varchon, F.; Mallet, P.; Magaud, L.; Veuillen, J.-Y. (Phys. Rev. B, 2008)

(untitled) - Varchon, F.; Mallet, P.; Veuillen, J.-Y.; Magaud, L. (Phys. Rev. B, 2008)

(untitled) - Li, G.; Luican, A.; Andrei, E. Y. (Phys. Rev. Lett., 2009)

(untitled) - Allen, M. J.; Tung, V. C.; Kaner, R. B. (Chem. Rev., 2011)

(untitled) - Sakai, K.-i.; Takai, K.; Fukui, K.-i.; Nakanishi, T.; Enoki, T. (Phys. Rev. B, 2010)

(untitled) - Phark, S.-h.; Borme, J.; Vanegas, A. L.; Corbetta, M.; Sander, D.; Kirschner, J. (ACS Nano, 2011)

(untitled) - Yang, H.; Mayne, A. J.; Boucherit, M.; Comtet, G.; Dujardin, G.; Kuk, Y. (Nano Lett., 2010)

(untitled) - Tapasztó, L.; Dobrik, G.; Lambin, P.; Biró, L. P. (Nat. Nanotechnol., 2008)

(untitled) - Cai, J.; Ruffieux, P.; Jaafar, R.; Bieri, M.; Braun, T.; Blankenburg, S.; Muoth, M.; Seitsonen, A. P.; Saleh, M.; Feng, X.; Mullen, K.; Fasel, R. (Nature, 2010)

(untitled) - Park, C.; Yang, H.; Mayne, A. J.; Dujardin, G.; Seo, S.; Kuk, Y.; Ihm, J.; Kim, G. (Proc. Natl. Acad. Sci. U. S. A., 2011)

(untitled) - Sun, Z.; Pint, C. L.; Marcano, D. C.; Zhang, C.; Yao, J.; Ruan, G.; Yan, Z.; Zhu, Y.; Hauge, R. H.; Tour, J. M. (Nat. Commun., 2011)

Noncontact Atomic Force Microscopy - Morita, S.; Giessibl, F. J.; Wiesendanger, R. (Springer, 2009)

(untitled) - Todorov, I. T.; Smith, W.; Trachenko, K.; Dove, M. T. (J. Mater. Chem., 2006)

(untitled) - Bocquet, F.; Nony, L.; Loppacher, C.; Glatzel, T. (Phys. Rev. B, 2008)

(untitled) - Nony, L.; Foster, A. S.; Bocquet, F.; Loppacher, C. (Phys. Rev. Lett., 2009)

Kelvin Probe Force Microscopy - Measuring, Compensating Electrostatic Forces - Sadewasser, S.; Glatzel, T. (Springer, 2012)

(untitled) - Tersoff, J. (Phys. Rev. B, 1989)

(untitled) - van Duin, A. C. T.; Dasgupta, S.; Lorant, F.; Goddart, W. A., III (J. Phys. Chem. A, 2001)

(untitled) - Bosson, M.; Grudinin, S.; Bouju, X.; Redon, S. (J. Comput. Phys., 2012)

(untitled) - Lewis, J. P.; Jelínek, P.; Ortega, J.; Demkov, A. A.; Trabada, D. G.; Haycock, B.; Wang, H.; Adams, G.; Tomfohr, J. K.; Abad, E.; Wang, H.; Drabold, D. A. (Phys. Status Solidi B, 2011)

(untitled) - Sadewasser, S.; Jelinek, P.; Fand, C.-K.; Custance, O.; Yamada, Y.; Sugimoto, Y.; Abe, M.; Morita, S. (Phys. Rev. Lett., 2009)

(untitled) - Tsukada, M.; Masago, A.; Shimizu, M. (J. Phys.: Condens. Matter, 2012)

(untitled) - Dappe, Y. J.; Basanta, M. A.; Flores, F.; Ortega, J. (Phys. Rev. B, 2006)

(untitled) - Dappe, Y. J.; Scipioni, R. (Phys. Rev. B, 2011)

(untitled) - Seydou, M.; Dappe, Y. J.; Marsaudon, S.; Aimé, J.-P.; Bouju, X.; Bonnot, A.-M. (Phys. Rev. B, 2011)

(untitled) - Argento, C.; French, R. H. (J. Appl. Phys., 1996)

(untitled) - Tang, H.; Bouju, X.; Joachim, C.; Girard, C.; Devillers, J. (J. Chem. Phys., 1998)

(untitled) - Allinger, N. L.; Chen, K.; Lii, J.-H. (J. Comput. Chem., 1996)

(untitled) - Allinger, N. L. (J. Comput.-Aided Mol. Des., 2011)

(untitled) - de Brito Mota, F.; Justo, J. F.; Fazzio, A. (J. Appl. Phys., 1999)

(untitled) - Lindsay, L.; Broido, D. A. (Phys. Rev. B, 2010)

(untitled) - Kawai, S.; Glatzel, T.; Koch, S.; Such, B.; Baratoff, A.; Meyer, E. (Phys. Rev. B, 2010)

(untitled) - Wright, C. A.; Solares, S. D. (Nano Lett., 2011)

(untitled) - Sun, Z.; Hämäläinen, S. K.; Sainio, J.; Lahtinen, J.; Vanmaekelbergh, D.; Liljeroth, P. (Phys. Rev. B, 2011)

(untitled) - Campbellová, A.; Ondráček, M.; Pou, P.; Pérez, R.; Klapetek, P.; Jelínek, P. (Nanotechnology, 2011)

(untitled) - Canova, F. F.; Foster, A. S. (Nanotechnology, 2011)

(untitled) - Kolmogorov, A. N.; Crespi, V. H. (Phys. Rev. B, 2005)

(untitled) - Lampin, E.; Priester, C.; Krzeminski, C.; Magaud, L. (J. Appl. Phys., 2010)

(untitled) - Filleter, T.; Bennewitz, R. (Phys. Rev. B, 2010)

(untitled) - Girit, C. O.; Meyer, J. C.; Erni, R.; Rossell, M. D.; Kisielowski, C.; Yang, L.; Park, C.-H.; Crommie, M. F.; Cohen, M. L.; Louie, S. G.; Zettl, A. (Science, 2009)

(untitled) - Koskinen, P.; Malola, S.; Häkkinen, H. (Phys. Rev. B, 2009)

(untitled) - Coraux, J.; N’Diaye, A. T.; Engler, M.; Busse, C.; Wall, D.; Buckanie, N.; Meyer zu Heringdorf, F. J.; Van Gastel, R.; Poelsema, B.; Michely, T. (New J. Phys., 2009)

(untitled) - Hämäläinen, S. K.; Sun, Z.; Boneschanscher, M. P.; Uppstu, A.; Ijäs, M.; Harju, A.; Vanmaekelbergh, D.; Liljeroth, P. (Phys. Rev. Lett., 2011)

(untitled) - Koskinen, P.; Malola, S.; Häkkinen, H. (Phys. Rev. Lett., 2008)

(untitled) - Kroes, J. M. H.; Akhukov, M. A.; Los, J. H.; Pineau, N.; Fasolino, A. (Phys. Rev. B, 2011)

(untitled) - Rodrigues, J. N. B.; Gonçalves, P. A. D.; Rodrigues, N. F. G.; Ribeiro, R. M.; Lopes dos Santos, J. M. B.; Peres, N. M. R. (Phys. Rev. B, 2011)

(untitled) - Guo, Y.; Guo, W. (J. Phys. Chem. C, 2011)

(untitled) - Touhari, F.; Bouju, X.; Girard, C.; Devel, M.; Cohen-Solal, G. (Appl. Surf. Sci., 1998)

(untitled) - Bouju, X.; Girard, C.; Labani, B. (Ultramicroscopy, 1992)

(untitled) - Girard, C.; Bouju, X.; Joachim, C. (Chem. Phys., 1992)

(untitled) - Girard, C.; Bouju, X.; Martin, O. J. F.; Dereux, A.; Chavy, C.; Tang, H.; Joachim, C. (Phys. Rev. B, 1993)

(untitled) - Kantorovich, L. N. (J. Phys.: Condens. Matter, 2001)

(untitled) - Trevethan, T.; Kantorovich, L. (Nanotechnology, 2004)

(untitled) - Polesel-Maris, J.; Venegas de la Cerda, M. A.; Martrou, D.; Gauthier, S. (Phys. Rev. B, 2009)